LITERATURE REVIEW: RELATIONSHIP BETWEEN ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) ON FINANCIAL PERFORMANCE (FP) - Rinda Fithriyana; Fajri Adrianto; Rida Rahim (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This literature review article discusses the relationship between environmental, social and corporate governance (ESG) on the company's financial performance. By using a systematic literature review method, this article tries to collect various research results on ESG-FP. By using the main theory of stakeholders and agency theory.